F-106 Transition state Gp120 structures as HIV vaccines. (January 2016) - DeVico, Anthony; Fouts, Timothy; Schwartz, Jennifer; Gilliam, Bruce; Redfield, Robert; Gallo, Robert; Lewis, George
Abstract : Protective efficacy from an HIV vaccine will heavily depend on anti-envelope antibodies that block the entry and spread of diverse viral strains. Thus, an HIV vaccine will have to generate humoral responses that selectively recognize highly conserved and functional epitopes. Accordingly, we have been developing HIV vaccine strategies based on observations that very highly conserved epitopes are presented on HIV gp120 as it transitions through different structural states during viral entry. Here we will cover the virological basis for this approach; describe an immunogen (FLSC) designed to mimic transition state gp120 structures; discuss how the immunogenicity of FLSC is linked with humoral effector functions, protective efficacy and virion recognition; describe our progress in the clinical manufacture of FLSC; and outline immediate plans for Phase I clinical testing.